The effect of glycine on the growth of the miscroalgae spirulina platensis - Kotynskyy, Andriy; Salyuk, Anatoly (My University, 2013)
Bringing glycine in a culture medium leads to the intensification of spirulina’s growth and accumulation of its biomass. Glycine provides the fragmentation of microalgae’s trichomes. The intensity of the fragmentation in this case depends on the concentration of the brought in glycine and on the phase of culture’s growth it is brought in.
Keywords: accumulation of biomass; fragmentation trichomes; spirulina platensis; glycine; накопление биомассы; фрагментация трихом; spirulina platensis; глицин; накопичення біомаси; фрагментація трихом; spirulina platensis; гліцин; кафедра екології та екоменеджменту